Half a century of cropland change. - Hart, John Fraser (Geographical Review, 2001)
The census concept of total cropland is a better measure of effective agricultural land than is total farmland, which includes extensive areas of woodland owned by farmers. The cropland area of the United States dropped from 478 million acres in 1949 to 431 million acres in 1997, for a net loss of less than 1 million acres, or roughly one-fifth of 1 percent, per year. In the midwestern agricultural heartland most counties changed less than 5 percent in the half-century, and more counties gained than lost. The West was a crazy quilt of change, and in the East most counties lost more than 10 percent. Major metropolitan counties lost a few percentage points more than did adjacent areas, but at a lower rate per capita than the nation as a whole. Most of the loss of cropland was in marginal agricultural counties with soils of low inherent fertility and topography unsuited to modern farm machinery. The loss of cropland to suburban encroachment may be cause for intense local concern, but attempts to thwart development cannot be justified on grounds of a net national loss of good cropland. Reprinted by permission of the publisher.